The Use of Memberwise Disjunction Mechanism to Select Teaching Methods Depending on Student Personality Type - Roman Zinko; Maria Ivanchenko; Uliana Hanas (Studia Periegetica, 2017)
The problem of teaching methods classification doesn't lose its importance nowadays, because it gives the opportunity to analyze each method potential and to identify ways for its improvement, further development and implementation. A large number of approaches to teaching methods classification exists due to the complexity of the study object and seriousness of the tasks set by society before the modern professional school. The use of the memberwise disjunction mechanism in training methods classification which allows to take to the account wider range of different teaching methods symptoms is proposed. Visualization of the proposed classification with the help of graphs preserves the informational content of the multivariate data in a convenient, human-readable form, simplifies the perception of such classification and focuses attention on its features. Depending on the objectives of effective learning provision, it is possible to change the dominant criteria, and accordingly choose an effective, in this case, teaching methods. In the given example, a logical connection between teaching methods and students' types of consciousness and thinking is shown.(original abstract)